International Classification of Functioning, Disability and Health (ICF) and correlation between disability and finance assets in chronic stroke patients - Marotta, Nicola; Ammendolia, Antonio; Marinaro, Cinzia; Demeco, Andrea; Moggio, Lucrezia; Costantino, Cosimo (Acta Biomedica Atenei Parmensis, 2020)
Background. Stroke is the third cause of long term disability worldwide and its rehabilitation program must to have into account all aspects of disability. International research and politics increasingly study the relationship between disability and the direct costs associated with living with a disability. Objective. Using the ICF, this article provides a correlation between financial assets and disability in participation and activities, in a context such as the Italian one where there is a twenty-year decentralization of the national health system Methods. At the University of Catanzaro, in southern Italy, n=130 ICF checklists of stroke patients were analyzed at 6 months from the end of the rehabilitation treatment. Financial assets domains in environment and nine domains in participation and activities were correlated, in order to evaluate the relationship between familiar economic condition and disability. Results. Pearson’s r test (t = -6.6515, df = 25, p-value<0.05) showed a significant correlation of 0.79. Multiple R-squared was 0.639 and an we reported an Adjusted R-squared of 0.6245 (p<0.05). Thus, about 62% of the increase of the all considered disability qualifiers in participation and activities in ICF checklist can be explained by a lower financial income. Conclusions. In a regional context (Calabria) of an European country (Italy) with a national health system, thanks to the ICF it can be assumed that with the decrease of the financial income, the gap in participation of activities increases.